2003
DOI: 10.1038/sj.bjc.6600755
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of local relapse in high-risk breast cancer patients: can radiotherapy fractionation and time factors make a difference?

Abstract: Large primary breast tumours and extensive lymph node involvement are linked to a high rate of local recurrence after surgery. In 10 -20% of such high-risk breast cancer patients, local relapse will occur despite postoperative radiotherapy. In the present study, we investigated whether molecular features, such as angiogenesis, cancer cell proliferation, steroid receptor expression, c-erbB-2 oncoprotein overexpression, p53 protein nuclear accumulation or bcl-2 antiapoptotic protein expression, can predict failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…Previous studies have assessed the usefulness of biomarkers, such as Ki-67 and p53, and multi-gene signatures, such as wound response signature and the Oncotype DX assay, as indicators of local recurrence [38][39][40]. We suggest that the interaction of patient age with these and other biomarkers be considered in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have assessed the usefulness of biomarkers, such as Ki-67 and p53, and multi-gene signatures, such as wound response signature and the Oncotype DX assay, as indicators of local recurrence [38][39][40]. We suggest that the interaction of patient age with these and other biomarkers be considered in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…A previous pilot study showed that hypofractionated accelerated RT with cytoprotection using intravenously administered amifostine (HypoARC) provided encouraging results, with minimal early and late toxicity and improved efficacy in specific subgroups of patients (8,9). Since 2003, a prospective study has been on-going, recruiting patients with early-stage breast cancer to receive HypoARC to the breast and/or axilla and supported with high-dose, daily, subcutaneously administered, amifostine.…”
Section: Introductionmentioning
confidence: 93%
“…An immunohistochemical streptavidin-biotin technique was used for the detection of c-erbB-2 and estrogen receptor (ER) expression, as previously described (9). The percentage of tumor cells with membrane c-erbB-2 staining was recorded in all optical fields, and a mean value of $20% was considered positive.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In oesophageal, head and neck tumours, microvessel density or vascular grade was predictive of response (178–181). Recurrences after wide local excision and radiation therapy showed no association with tumour VEGF expression (182) and highly vascular tumours recurred after aggressive regimens such as hypofractionated and accelerated radiotherapy despite being more effective in tumours with high proliferation, c‐erbB‐2 and p53 overexpression (183).…”
Section: Clinical Applications Of Histological Quantitation Of the Tumentioning
confidence: 99%